Case report: Double-chambered right ventricle diagnosed in a middle-aged female with hypertrophic cardiomyopathy and atrial flutter: A rare case - Ge, Junye; Hu, Tong; Liu, Yan; Wang, Qian; Fan, Guanqi; Liu, Chuanzhen; Zhang, Jun; Chen, Shiming; Maduray, Kellina; Zhang, Yun; Chen, Tongshuai; Zhong, Jingquan (Frontiers in Cardiovascular Medicine, 2022)
Double-chambered right ventricle (DCRV) is a rare congenital heart defect in adults, manifesting with progressive right ventricular outflow tract obstruction. We describe the first case of DCRV coexisting with hypertrophic cardiomyopathy which are complicated by atrial flutter. A middle-aged woman who complained of recurrent symptomatic atrial flutter was admitted to our department with a diagnosed biventricular hypertrophic cardiomyopathy history. Echocardiography and cardiac magnetic resonance revealed asymmetrical interventricular septal hypertrophy, abnormal muscle bundles within the right ventricle, generating an obstructive gradient. Genetic testing detected one hypertrophic cardiomyopathy-associated mutation: MYH7, c.4135G>A, p. Ala1379Thr. A diagnosis of DCRV complicated by hypertrophic cardiomyopathy and atrial flutter was made. Surgical intervention was performed including radiofrequency ablation, abnormal muscle bundles removal and ventricular septal defect repair. Intraoperative transesophageal echocardiography demonstrated well-corrected right ventricular outflow tract obstruction. The patient was discharged in sinus rhythm on the 11th day after surgery without early post-operative complications. Unfortunately, the patient died from a sudden death 38 days after surgery. In conclusion, the coexistence of DCRV with hypertrophic cardiomyopathy in patients is an uncommon condition. The present case highlights the importance of imaging in diagnosis of this entity.